Building approval data and the quantification of sustainability over time. Issue 2 (11th May 2015) - Wilkinson, Sara
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The fifth IPCC report on climate change concluded current progress to mitigate anthropocentric climate change is not making any impact. As the built environment emits 50 percent of total greenhouse gas emissions, mitigating climate change through sustainable construction and adaptation is a priority. Although many new buildings have sustainability ratings, they comprise a minute amount of the total stock. Meanwhile policy makers are adopting strategies to become carbon neutral with targets that require measurement. The purpose of this paper is to propose a means of quantifying the uptake of sustainability across all stock over time using existing policy frameworks. Design/methodology/approach – Given that this is a scoping study to explore the potential to adapt existing frameworks to facilitate the quantification of the uptake of sustainability measures over time, the research adopted a focus group technique with experienced stakeholders in Australia and England. Qualitative research is inductive and hypothesis generating. That is; as the research assimilates knowledge and information contained in the literature ideas and questions are formed, which are put to research participants and from this process conclusions are drawn. Findings – It is technologically feasible to collect data on sustainability measures within the building approvals systems in Victoria and NSW Australia and England and Wales and a conceptual model is proposed. Economically, costs need to be covered, and it is unclear which group should pay. Socially, the benefits would be to determine how society is progressing towards goals. The benefits of achieving reduced carbon emissions would be mitigation of the predicted changes to climate and informing society of progress. Politically, it is unlikely there is a will to make provisions for this proposal in existing regulatory systems. Research limitations/implications – The key limitations of the research were that the views expressed are those of a select group of experienced practitioners and may not represent the consensus view of the professions and industry as a whole. The limitations and criticisms of focus group data collection are that the sessions may be dominated by individuals holding strong views. Practical implications – The findings show that adaptation of the existing data collected by building control authorities could allow some quantification of the uptake of sustainability measures over time. A simple initial system could be implemented with relative ease to ascertain the value of the data. Over time the system could be extended to collect more data that could facilitate more precise quantification of sustainability. Significantly policy makers would have a tool that would allow them to measure the success or otherwise of mandatory and voluntary measures introduced to increase the uptake of sustainability. Originality/value – To date, no one has considered the practicality or potential utility of adapting existing information gathered for building approval purposes for the quantification of the up-take of sustainability across the whole stock over time. The value of using building approval data are that all building types are required to have building approvals prior to work being undertaken.